2009
DOI: 10.1542/peds.2008-2793
|View full text |Cite
|
Sign up to set email alerts
|

Time-Related Changes in Steroid Use and Bronchopulmonary Dysplasia in Preterm Infants

Abstract: Steroid use and preference have changed significantly over the past decade. Decreased use of DEX was associated with increased rates of BPD, any or severe, among very preterm infants. Well-designed, randomized, noncrossover trials with long-term outcome analysis of high-risk infants are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
67
2
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 93 publications
(72 citation statements)
references
References 24 publications
2
67
2
1
Order By: Relevance
“…[212][213][214] The recent meta-regression that demonstrated that corticosteroids will decrease the risk of poor neurodevelopmental outcome if an infant's baseline risk of developing BPD is Ͼ55%, along with recent updates of the Cochrane reviews, have affected our thinking. [215][216][217] 221 Confirmation of this and other new predictive tools are needed.…”
Section: Perception: the Lack Of Useful Therapies Forces Us To Revisimentioning
confidence: 99%
“…[212][213][214] The recent meta-regression that demonstrated that corticosteroids will decrease the risk of poor neurodevelopmental outcome if an infant's baseline risk of developing BPD is Ͼ55%, along with recent updates of the Cochrane reviews, have affected our thinking. [215][216][217] 221 Confirmation of this and other new predictive tools are needed.…”
Section: Perception: the Lack Of Useful Therapies Forces Us To Revisimentioning
confidence: 99%
“…Sin embargo, su uso se ha asociado en diversos estudios con efectos adversos a corto y largo plazo, como hipertensión arterial sistémica, hiperglucemia, retraso en el crecimiento, perforación intestinal, hemorragia digestiva, cardiomiopatía hipertrófica, infección y alteraciones en el neurodesarrollo (1)(2)(3). Por ello, en el 2002, la Canadian Paediatric Society y la American Academy of Pediatrics recomendaron evitar el uso rutinario de corticoides para la prevención y el tratamiento de la displasia pulmonar (4)(5)(6)(7)(8).…”
unclassified
“…While, the therapeutic efficacy of HC to treat or prevent CLD is debatable, the present studies and previous clinical reports serve to indicate that HC treatment is probably safer than Dex in the neonatal brain. Due to the concern of adverse effect on neurodevelopment, the use of Dex has dropped dramatically to ~10% of the preterm infants at risk for CLD (20), which is associated with increased rate of severe CLD (21). Current evidence strongly suggests that the benefits of early or late postnatal corticosteroid treatment, particularly Dex, may not outweigh the known or potential adverse effects of the treatment (8,22).…”
Section: Articlesmentioning
confidence: 99%